(untitled) (Modern education and development, 2025)
Мақолада тасвирий саньатда “Қоралама”(Набросок)нинг мохияти, рассом учун мухим жараён эканлиги ёритилган. Рассом ҳар доим қоғоз ва қалам билан тезкор хомаки чизгилар чиза олиши қадимдан бизгача етиб келган мухим амалий машғулот саналади. Ушбу мақолада қоралама ҳақида илмий таҳлиллар ва рассом-талабалар фаолиятидаги махоратни оширишга қаратилган ушбу жараённинг тасвирий саньатдаги ахамияти тўғрисида фикрлар ёритилган. The article explores the essence of "sketching" in visual arts and its significance as a crucial process for artists. The ability of an artist to quickly create preliminary drawings with paper and pencil has been an essential practical exercise passed down through generations. This article presents a scientific analysis of sketching and discusses its importance in enhancing the skills of art students, emphasizing its role in visual arts.